2005
DOI: 10.1007/s00428-005-1262-y
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant deregulation of HIF1α and cell cycle proteins in VHL-mutated renal cell carcinomas

Abstract: Renal cell carcinomas (RCCs) of the clear cell type are associated with alteration of the von Hippel-Lindau (VHL) tumour suppressor gene as well as subsequent stabilization and over-expression of hypoxia inducible factor (HIF), which causes up-regulation of cyclin D1. On the basis of their ability to interact with cyclin D1 we investigated a number of cell cycle proteins to shed further light on the downstream effects of HIF dysregulation. Expression of HIF1alpha, cyclin D1, cyclin-dependent kinase 4 and cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…As evident in Fig. 1B, HIF-1 activity was nondetectable under normoxic growth conditions showing the absence of aberrant signaling pathways resulting in stable expression of HIF-1 (10). The immunoblot data show that these cells produced large amounts of EGFP following treatment with CoCl 2 , with optimal concentrations in the range of 200 to 300 Amol/L.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…As evident in Fig. 1B, HIF-1 activity was nondetectable under normoxic growth conditions showing the absence of aberrant signaling pathways resulting in stable expression of HIF-1 (10). The immunoblot data show that these cells produced large amounts of EGFP following treatment with CoCl 2 , with optimal concentrations in the range of 200 to 300 Amol/L.…”
Section: Resultsmentioning
confidence: 76%
“…However, another caveat of using the HRE system in tumors is the variation of normal HIF-1a expression levels in cancer cell lines where the expression can be independent of oxygen tension (10). This dysregulation is brought about by several pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it has been shown that over-expression of HIF-1a induced by hypoxia was paralleled by down-regulation of the cyclin-dependent kinase inhibitor p27. In the same way, reduction or absence of p27 abrogated the hypoxia-induced G1 checkpoint, also suggesting that p27 is a key regulator of G1/S transition in hypoxic cells [23,24].…”
mentioning
confidence: 72%